USERâS ACCEPTANCE OF BIOMETRIC AUTHENTICATION SYSTEM - Dona Sunandi, Salsabila
The rising of document fraud and identity theft, alongside new threats such as cybercrime, has led to the understandable changes that need to be undertaken in a whole new approach. Biometric authentication comes as a solution, which refers to the application of computational methods to biological features, especially about the study of unique biological characteristics of human (Hopkins, 1999). It has successfully established itself as a relevant manner to identify and authenticate individuals in a reliable and fast way by using an individual’s unique biological characteristics. The use of biometric systems for personal authentication is a response to the rising issue of authentication and security. This paper aims to determine the factors that influence the user’s acceptance of using a biometric authentication system that involves 1000 university students in Indonesia. To examine the user’s acceptance of using biometric authentication system, this paper integrates the advanced version of Technology Acceptance Model (TAM) and analyze the data using Statistical Package for Social Science (SPSS) and to discover the relationship between independent and dependent variables, this paper adopts the extension of multiple linear regression, namely path analysis to find the possible causal chain between the associated variables. The results indicate that all factors are significantly affecting the user’s acceptance of using biometric authentication system with 0.000 significance value as a better security measure to customers except one variable notably social influence, showing that it does not statistically significantly related with the behavioral intention to use. The most influential variables go into perceived usefulness, accounting for 0.465 by totalizing up both direct and indirect influence. The second goes into attitude towards usage with 0.347 and the third goes into new product attribute, scoring 0.1924 by also totalizing up both direct and indirect impact. These findings represent the willingness to accept the biometric authentication system to provide better protection of confidential data. Such banks, e-commerce, and online application could incorporate this system to enhance the security of its users better.